Genome-Wide CRISPR Screening Identifies JAK1 Deficiency as a Mechanism of T-Cell Resistance - Han, Ping; Dai, Qiang; Fan, Lilv; Lin, Hao; Zhang, Xiaoqing; Li, Fanlin; Yang, Xuanming (Frontiers in Immunology, 2019)
Somatic gene mutations play a critical role in immune evasion by tumors. However, there is limited information on genes that confer immunotherapy resistance in melanoma. To answer this question, we established a whole-genome knockout B16/ovalbumin cell line by clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR-associated protein-9 nuclease technology, and determined by in vivo adoptive OT-I T-cell transfer and an in vitro OT-I T-cell-killing assay that Janus kinase (JAK)1 deficiency mediates T-cell resistance via a two-step mechanism. Loss of JAK1 reduced JAK-Signal transducer and activator of transcription signaling in tumor cells—resulting in tumor resistance to the T-cell effector molecule interferon—and suppressed T-cell activation by impairing antigen presentation. These findings provide a novel method for exploring immunotherapy resistance in cancer and identify JAK1 as potential therapeutic target for melanoma treatment.